The preparation and characterization of Au/HZSM-5 catalyst and its application in CH4 adsorption - Nulahong1, A.; Wenlong, Mo; Fengyun, Ma; Aldabergenova, S. (Вестник Карагандинского университета, 2016)
Au/HZSM-5 catalysts were prepared by negative deposition-precipitation method in this paper. XRD/Uvvis/ TEM/NH3-TPD/FT-IR technologies were used to analysis the characterization of prepared catalysts, and the evaluation of the catalysts was carried out by methane adsorption experiment. XRD and TEM showed that 2.0Au/ HZSM-5 catalyst calcined under N2 atmosphere held metal particle size about 5–10 nm; Uv-vis indicated that the method of calcination changed Au from ion-valent state to zero-valent state, and the zero-valent absorption peak of 2.0Au/HZSM-5 catalyst calcined under N2 atmosphere was weaker, which indicated that its corresponding particle size was smaller; NH3-TPD showed that the peak area of relatively strong acid center of Au/HZSM-5 catalyst declined respect to HZSM-5; FT-IR showed that the Au/HZSM-5 catalysts could convert methane to adsorbed species containing olefin double bond at low temperature, showing better C–H bond activation capability for methane.
Keywords: Au/HZSM-5; catalyst; methane; adsorption